Perkembangan Pembiayaan Multi Akad di Indonesia: Studi Pendekatan NVivo dan Literatur Review - Doni Yusuf Bagaskara; Rohmadi; Nanik Wahyuni (At-Tasharruf "Jurnal Kajian Ekonomi dan Bisnis Syariah", 2024)
This study aims to determine the development of multi-contract financing in Indonesia using the NVivo approach. This research uses qualitative methodology with Nvivo approach and literature review. "Data analysis techniques include: (1) mapping the number of news article codes based on qualitative analysis using Nvivo 14 software around "Multi Akad", (2) mapping visualization results with hierarchical diagrams and testing the correlation of relationships between media articles using Nvivo 14 software; (3) map the research topic with the World Cloud or a collection of words that are often discussed in media articles; and (4) test the significant value between media articles to determine the size or size of a correlation around the topic "Multi Akad". The results of this study show that the topics that are often discussed in media articles about Multi Akad are the understanding and law of multi. While the topic that is rarely discussed by media articles about Multi Akad is the understanding and examples of the implementation of Multi Akad.